Analysis of Lombok Folktales (Cilinaya) Based on Vladimir Propp's Theory - Hendriani, Ria; Herman; suwandi (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2022)
This research is attempted to describe the types of character and function based on Vladimir Propp’s theory and focused on finding the characters and the functions of the folktales itself. In this research, the researchers were analyzed one of the folktales entitled Cilinaya. Cilinaya have many characters and functions that are appropriate to analyze by using Propp’s theory. Vladimir Propp extended the Russian formalis approach to narratology. Propp was able to arrive at typology of narratives structure by analyzing types of characters and kinds of action. Vladimir Propp’s theory is important part in narrative. His influence is clearly important within narrative history. His detail formula’s emphasizes his intelligence and the importance of his theory. The researchers were able to arrive at the conclusion that there were thirty-one generic narratives or functions in the folktale, while not all present in Cilinaya folktale. Cilinaya comprise seven characters instead of eight, ones which the same person is distributed among various characters, such as Jero Tuek and Adipati, they have many roles, as the villains, and the dispatchers. Cilinaya also fulfills twenty five functions not in order but still follows the sequence of the functions.